Primary Angioplasty for Cardiac Allograft Vasculopathy Presenting as ST-Elevation Acute Myocardial Infarction during Endomyocardial Biopsy - Bruno Ramos Nascimento; Thalles Oliveira Gomes; Júlio César Borges; Guilherme Rafael Sant’Anna Athayde; Sílvio Amadeu de Andrade; Maria da Consolação Vieira Moreira (Case Reports in Transplantation)
Cardiac allograft vasculopathy is still a major issue, with significative mortality in heart transplant patients, and the best therapeutic options are not yet established. The progressively higher survival rates after transplantation have made it a major concern. This is a case report about a patient who underwent cardiac transplantation due to chagasic cardiomiopathy. During an endomyocardial biopsy more than 2 years after the transplant, the patient arrested in ventricular fibrillation, with ST-elevation in anterior leads after defibrillation. The angiography showed total occlusion of proximal left anterior descending artery, promptly treated with primary angioplasty, with excellent angiographic and clinical results.